RESEARCH OF QUALITY OF PASSENGER WAGON CHANGES IN DESIGN LAYOUT BY MEANS OF DAMPING COMPUTER SIMULATION (Transport systems and technologies, 2018)
The article presents the studies to determine the effect of the presence of a structural scheme of dampers in the axle-box level hanging on driving performance of high-speedpassenger train on bogies without cradle suspension. On the basis of a computer model of the dynamics of a passenger car for the highspeed service in the software complex «Universal mechanism» calculated the dynamic performance of the carriage.
Keywords: damping carriage system, a computer model of the car, dampers, damping factor